Characterization of infectious and non-infectious gastrointestinal disease in common variable immunodeficiency: analysis of 114 patient cohort - Sanchez, David A.; Rotella, Karina; Toribio, Crhistian; Hernandez, Matthew; Cunningham-Rundles, Charlotte (Frontiers in Immunology, 2023)
Common Variable Immunodeficiency (CVID), a complex primary immunodeficiency syndrome defined by defective B cell responses to infection and vaccination, has heterogeneous clinical manifestations. Gastrointestinal (GI) complications in CVID, both infectious and non-infectious, can cause significant impairment leading to malabsorption and frank malnutrition. In order to better characterize the spectrum of GI disease associated with CVID, we describe 114 patients with GI disease (15.6%) from our 728 patient single center CVID cohort. Norovirus, Giardia and Cytomegalovirus were the most frequently isolated infectious pathogens. CVID enteropathy was the most encountered GI diagnosis based on endoscopy, with only a minority of patients having Crohn’s disease (6.1%) or ulcerative colitis/proctitis (4.5%). Concurrent autoimmunity (30.7%), lung disease (18.4%) and malignancy (8.7%) were also present in significant proportion of subjects. Lastly, 16 of 47 (34%) who underwent whole exome sequencing demonstrated a culprit gene defect associated with CVID.